(untitled) (Global Journal of Management and Business Research, 2017)
There has been some few definitions about what effective management of an organization should be, the structures to put in place so as to get the best administration of the organization. This study looks at the supply chain in the direction of an organization, its importance, and design. This study, however, concluded that it is useful for every business to have a supply chain in the organization since it does coordinate the people and activities within including those outside the organization and that it also maximize profit by eliminating unnecessary cost.